THU0560 Efficiency of Patient Education on Early Stage of Rheumatoid Arthritis. (10th June 2014) - Orlova, E.; Karateev, D.; Denisov, L.; Kochetkov, A.; Nasonov, E.
Abstract : Background: Patient education is an important component of the care for patients with rheumatoid arthritis (RA), giving the possibilities for self-management of the disease [1, 2]. Objectives: To develop the education program for patients with RA and to evaluate its efficiency on early stage of the disease. Methods: The group-education program was developed with the support of the Russian National Public Organization of Disabled People NADEZHDA (Hope) and consisted of 4 daily 90-min education lessons. All information was presented by a multidisciplinary team (rheumatologist, cardiologist, psychologist, physiotherapist and occupational therapist). 55 patients with early RA (83, 6% females, age of 18 to 62 years, disease duration of 2 to 22 months) were included. 25 study group patients were trained according to the education program, 30 received only drug therapy (control). Tender and swollen joint count, ESR, joint pain on 100-mm VAS, DAS28, HAQ, RAPID3, hand grip strength, the average powers of knee extension and ankle flexion by the EN-TreeM movement analysis were evaluated at baseline and following 3 and 6 months. Adherence to non-drug treatments was assessed by the special patient questionnaire. Results: After 3 and 6 months in the study group the adherence to joint protection strategies increased by 13, 0 and 10, 0 times (p<0, 01), to regular physical activity – by 4, 0 and 3, 25 times (p<0, 01), the compliance to use functional wrist orthoses – by 2, 0 times and 75, 0% (p<0, 01), knee orthoses – by 33, 3% and 50, 0% (p<0, 05), orthopedic insoles – by 71, 4% and 57, 1% (p<0, 01), respectively. After 6 months, there were statistically significant differences between the 2 groups in changes of most parameters (p<0, 05), excluding ESR, DAS28, the grip strength of a more affected hand and the extension power of a weaker knee (p>0, 05). 6 months following education program participation, there was significantly more frequently a good response to treatment according to the EULAR criteria (DAS28) (56, 3% vs 40, 0% in the control group, p<0, 05). Conclusions: The education program improves functional status and quality of life, helps to control diseases activity in patients with early RA within 6 months. Patient education enhances adherence to non-drug therapies. The maximum positive result was achieved after 3 months; this effect slightly diminished at 6 months. This necessitates retraining in the following 3–6 months. References: Riemsma RP, et al. Cochrane Database Sys Rev 2003;2:CD003688. Ellard DR, et al. Musculoskeletal Care 2009;7(1):17–30. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3737